"I appreciate your body, because…" Does promoting positive body image to a friend affect one's own positive body image?. (March 2021) - Alleva, Jessica M.; Medoch, Melissa M.; Priestley, Kira; Philippi, Johanna L.; Hamaekers, Jolien; Salvino, Eva N.; Humblet, Sanne; Custers, Marieke
Highlights: We tested effects of promoting positive body image to others on one's own body image. Expressing appreciation for a friend's body functionality improved one's body image. Yet, expressing appreciation for shared memories with a friend did, too. Improvements were found in both state functionality appreciation and state body appreciation. Abstract: Research has shown that individuals with a positive body image promote positive body image to others, yet also have close others who unconditionally accept their body and feel positively about their own body, too. This mutual interdependence between the individual and the environment with respect to positive body image has been termed reciprocity . Inspired by this research, we investigated whether promoting positive body image to others leads to improvements in one's own positive body image. To do so, undergraduate women ( N = 154) were randomised to write a letter to a friend, expressing either appreciation for their friend's body functionality (experimental group) or appreciation for their shared memories (control group). Participants completed pretest and posttest measures of state functionality appreciation and state body appreciation, and filler items. Unexpectedly, there were no group differences in state functionality appreciation and state body appreciation. Instead, participants within both groups experienced medium to large improvements in state functionality appreciation and state body appreciation. To our knowledge, this is the first study to test the effects of promoting positive body image to others. Future research can shed further light on the effects of promoting positive body image to others in particular, and on the phenomenon of reciprocity more broadly.